2023
DOI: 10.3390/f15010078
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Charcoal Production on Southern Angolan Miombo and Mopane Woodlands

Raquel Kissanga,
Luís Catarino,
Cristina Máguas
et al.

Abstract: About 80% of Angola’s forest surface is covered by Miombo and Mopane woodlands, which are explored for diverse activities such as fuelwood and food. This study aimed to assess the recovery dynamics of Miombo and Mopane woodlands after the selective cutting of tree species for charcoal production. For that, the structure and composition of plant communities in 37 plots, located in southwestern Angola, were characterized in fallows of different ages. Results showed that the diameter at breast height, basal area,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 74 publications
(87 reference statements)
3
4
0
Order By: Relevance
“…Ptaeroxylon obliquum , which was the species most cited by our informants, had an abundance of about 13 individuals/ha (PAI: 2.2). Similar density values have been found by [ 78 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Ptaeroxylon obliquum , which was the species most cited by our informants, had an abundance of about 13 individuals/ha (PAI: 2.2). Similar density values have been found by [ 78 ].…”
Section: Resultssupporting
confidence: 91%
“…nr = not reported. Species PAI Conservation Categories Inventory (Urso 2014) [ 77 ]: Only Adult Stems Inventory (Kissanga et al 2024) [ 78 ]: Adult and Young Stems Da Costa et al (2019) [ 80 ] IUCN (2023) [ 79 ] Average density (stems/ha) Aloe littoralis 2.9 LC 12.2 nr Aloe zebrina 2.8 LC nr nr Cassia angolensis 2.1 nr nr Cassytha filiformis 2.0 nr nr Cissampelos mucronata 1.0 nr nr Cissus quadrangularis 1.7 LC nr nr …”
Section: Table A1mentioning
confidence: 99%
“…[19], who noted that they were among the most preferred by charcoal producers in the Lubumbashi region. This is consistent with the Miombo in Angola, where most species used in carbonization belong to the Fabaceae [60]. The fruit tree species used in the rural area of Lubumbashi have been identified as being representative of the Miombo [61].…”
Section: Tree Species Used For Charcoal Productionsupporting
confidence: 76%
“…[58] from Madagascar, where the use of non-dried wood for carbonization led to a moisture content of 34%. The wood moisture content influences the time taken for the carbonization to occur [59,60], as demonstrated by the results of Ref. [49], who showed that wood moisture content below 30% can decrease the carbonization time in a kiln.…”
Section: Characteristics Of Kilnsmentioning
confidence: 99%
“…Much of the existing infrastructure was built well before independence, which took place in 1975. Angola is potentially one of the richest countries in the world in mineral and natural resources [21]. Oil production and its supporting activities contribute to approximately 50% of GDP, more than 70% of government revenues, and more than 90% of the country's exports [20,22] The unemployment rate in Angola reaches almost half of the population, and approximately 70% of Angolans live below the poverty line (with less than US$ 2 per day), with poverty being more prevalent in rural areas (58%) than in urban areas (19%) [20].…”
Section: Angola Overviewmentioning
confidence: 99%